Albert Einstein - Romero, Libby (Washington, D.C. : National Geographic, 2016)
Explore one of the most recognized scientists in the world, physicist Albert Einstein.
Who was Albert Einstein? -- Growing up in Germany -- In his time -- Educating Einstein -- Miracle year -- 6 cool facts about Einstein -- Research and reward -- A final quest.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes index.
Ages 6-9.
Description based on print version record.
Keywords: Einstein, Albert, -- 1879-1955 -- Juvenile literature; Physicists -- Biography -- Juvenile literature; Einstein, Albert, -- 1879-1955.; Einstein, Albert, -- 1879-1955.; Einstein, Albert, -- 1879-1955.; Physicists; Scientists; Physicists; Physicists; Scientists; Physicists -- Biography -- Juvenile literature; JUVENILE NONFICTION / Biography & Autobiography / Science & Technology; JUVENILE NONFICTION / Reader - Intermediate; JUVENILE NONFICTION / Science & Nature / History of Science; Electronic books- OSLIS; Biographies; Biography; Juvenile works; Biographies; Biography; Juvenile works; Electronic books